Genetic Variants Affecting Skeletal Morphology in Domestic Dogs. Issue 8 (August 2020) - Bannasch, Danika L.; Baes, Christine F.; Leeb, Tosso
Abstract : Purebred dog breeds provide a powerful resource for the discovery of genetic variants affecting skeletal morphology. Domesticated and subsequently purebred dogs have undergone strong artificial selection for a broad range of skeletal variation, which include both the size and shapes of their bones. While the phenotypic variation between breeds is high, within-breed morphological variation is typically low. Approaches for defining genetic variants associated with canine morphology include quantitative within-breed analyses, as well as across-breed analyses, using breed standards as proxies for individual measurements. The ability to identify variants across the genomes of individual dogs can now be paired with precise measures of morphological variation to define the genetic interactions and the phenotypic effect of variants on skeletal morphology. Highlights: Extreme differentiation in skeletal morphology characterizes purebred dog breeds. This has allowed the utilization of breed-average measurements or breed characteristics as phenotypes in subsequent genetic analyses. Across-breed association analysis has positively identified a relatively small number of loci (<20) for stereotypical dog breed body size. In outbred populations and within breeds there appear to be additional body size variants. In the face of high levels of inbreeding and very specific breed criteria for body size, less than 50% of the body size loci are fixed within breeds. Whole-genome sequence-based association approaches with millions of variants and modest numbers of animals facilitate the identification of new loci and the causative variants underlying canine skeletal morphology.